Penguatan Literasi Membaca Murid SD melalui Cerita Rakyat Kediri untuk Guru Kombel Sekartaji Kecamatan Mojoroto - Abdul Aziz Hunaifi; Endang Sri Mujiwati; Alfi Laila; Ita Kurnia; Encil Puspitoningrum; Alvina Venty Vaticasary; Imelda Angelina Wibowo (Jurnal Dharma Bhakti Ekuitas, 2026)
This community service activity aims to strengthen the reading literacy of elementary school students through the use of folk tales based on local wisdom in Kediri by teachers from the Sekartaji Learning Community in Mojoroto District, Kediri City. The main problems faced by partners include low student interest in reading, the dominance of conventional learning methods, and limited contextual and interesting reading materials. This program applies a contextual learning approach based on information and communication technology (ICT) through training and assistance in utilizing the Dongeng Nusantara educational portal. The implementation methods include preparation, socialization, technical training, collaborative workshops, as well as monitoring and evaluation. The results of the activity showed an increase in teacher competence of ≥80% in integrating local cultural values into literacy learning. In addition, teachers were able to independently develop story-based learning modules. The outputs of the activity, in the form of literacy modules and a collaborative network between teachers, support the sustainability of the program. This activity contributes to the achievement of Sustainable Development Goal (SDG) number 4 on quality education and the National Research Master Plan in the Social Humanities and Education cluster. The positive impacts include strengthening local cultural identity, increasing students' understanding of moral values, and the potential for replicating the program in other schools in the Kediri region. Keywords: community service, Kediri folk tales, nusantara fairy tale portal, reading literacy, sekartaji learning community Abstrak Kegiatan pengabdian masyarakat ini bertujuan memperkuat literasi membaca siswa sekolah dasar melalui pemanfaatan cerita rakyat berbasis kearifan lokal Kediri pada guru Komunitas Belajar Sekartaji di Kecamatan Mojoroto, Kota Kediri. Permasalahan utama mitra meliputi rendahnya minat baca siswa, dominasi metode pembelajaran konvensional, serta keterbatasan sumber bacaan yang kontekstual dan menarik. Program ini menerapkan pendekatan pembelajaran kontekstual berbasis teknologi informasi dan komunikasi (TIK) melalui pelatihan dan pendampingan pemanfaatan portal edukasi Dongeng Nusantara. Metode pelaksanaan meliputi tahap persiapan, sosialisasi, pelatihan teknis, workshop kolaboratif, serta monitoring dan evaluasi. Hasil kegiatan menunjukkan peningkatan kompetensi guru sebesar ≥80% dalam mengintegrasikan nilai-nilai budaya lokal ke dalam pembelajaran literasi. Selain itu, guru mampu mengembangkan modul pembelajaran berbasis cerita rakyat secara mandiri. Luaran kegiatan berupa modul literasi dan jejaring kolaboratif antar-guru mendukung keberlanjutan program. Kegiatan ini berkontribusi pada pencapaian Tujuan Pembangunan Berkelanjutan (SDGs) nomor 4 tentang pendidikan berkualitas dan Rencana Induk Riset Nasional di klaster Sosial Humaniora dan Pendidikan. Dampak positifnya mencakup penguatan identitas budaya lokal, peningkatan pemahaman siswa terhadap nilai-nilai moral, serta potensi replikasi program di sekolah lain di wilayah Kediri. Kata Kunci: pengabdian masyarakat, cerita rakyat Kediri, portal dongeng nusantara, literasi membaca, komunitas belajar sekartaji.